Geo-Immersive Learning: A Design Thinking Approach to Virtual Reality for Analyzing Multicultural Social Spaces - Diky Al Khalidy; Aulia Nindy Fadila Gastama; Balqis Salsabila; Dwiyono Hari Utomo; Sri Milawati Asshagab; Abid Febriansyah; Batchuluun Yembuu; Ha Van Thang (Unversitas Muhammadiyah Mataram, 2026)
Visualizing abstract concepts in Human Geography is challenging, and current Virtual Reality (VR) applications primarily address physical phenomena rather than social dynamics. To bridge this gap, this study aims to develop and evaluate VR-based learning media for the “Population Dynamics and Social Groups” material. The research employs a Research and Development (R&D) design using the Design Thinking model, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The development process emphasizes the novelty of integrating technical geospatial data, specifically astronomical coordinates and elevation, with a sociological analysis of three multicultural landscapes in Malang City: Chinatown (Pecinan), the Arab Quarter (Embong Arab), and the Madurese settlement. The subject of the implementation was undergraduate students of Geography Education at Universitas Negeri Malang. Data were collected using expert validation sheets and implementation observation sheets, then analyzed using descriptive quantitative techniques. The results demonstrate that the developed VR media is highly feasible for learning purposes. The quantitative analysis from the field implementation yielded an average observation score of 62.5 (out of a maximum of 68), classifying the product into the “Very Suitable” (Category A) category. Furthermore, qualitative observations indicated a significant increase in student enthusiasm and ease of understanding regarding the spatial distribution of social groups. This study concludes that integrating geospatial data with 360-degree visualization effectively bridges the gap between theoretical knowledge and field reality, offering a robust alternative to physical field trips.